Occupational exposure to animals and antibodies against Pasteurella multocida. Issue 12 (December 1987) - Choudat, D; Le Goff, C; Delemotte, B; Paul, G; Mady, V; Fages, J; Conso, F
Abstract : The relation between occupational exposure to cattle and prevalence of antibodies against Pasteurella multocida was evaluated in 680 workers. Three groups of exposed workers in abattoirs and slaughterhouses (S), in industrial breeding (I), and in traditional breeding (T) were compared with control workers not exposed to cattle or chicken (C). The prevalence of antibodies against capsular antigen A determined by indirect haemagglutination was significantly higher in the exposed groups (S: 26.2%; I: 29.0%; T: 32.1%) than in the control group (C: 14.0%). The prevalence of antibodies against capsular antigen D did not differ significantly between the groups. The prevalence of antibodies against one or more somatic antigens 1, 2, 3, 7, 8, or 9 was higher in the exposed groups with a significant difference only for group T versus group C (p less than 0.05). There was also a significant relation between antibodies against capsular antigen A and the contacts with pets. This high prevalence of antibodies against P multocida suggests that the infection is frequently subclinical and not only a disease associated with pets but also an occupationally related infection.